Proceedings 2019 Network and Distributed System Security Symposium 2019
DOI: 10.14722/ndss.2019.23206
|View full text |Cite
|
Sign up to set email alerts
|

The Crux of Voice (In)Security: A Brain Study of Speaker Legitimacy Detection

Abstract: A new generation of scams has emerged that uses voice impersonation to obtain sensitive information, eavesdrop over voice calls and extort money from unsuspecting human users. Research demonstrates that users are fallible to voice impersonation attacks that exploit the current advancement in speech synthesis. In this paper, we set out to elicit a deeper understanding of such human-centered "voice hacking" based on a neuro-scientific methodology (thereby corroborating and expanding the traditional behavioral-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Their results show that there is a significant increase in several areas of the brain when people view fake websites vs. real websites even though users' accuracy in identifying the legitimacy of the site was close to 50%. The study of [32] investigated users' processing of real vs. fake voices in the context of voice impersonation attacks, with similar findings as to the above studies. Stanford History Education Group conducted a study [18] in which the participants (school/college students) were asked to find the differences in some media contents, e.g., news and ads, identify real-fake Facebook accounts, test the reliability of Facebook posts (whether a web site is trusted).…”
Section: Related Workmentioning
confidence: 67%
“…Their results show that there is a significant increase in several areas of the brain when people view fake websites vs. real websites even though users' accuracy in identifying the legitimacy of the site was close to 50%. The study of [32] investigated users' processing of real vs. fake voices in the context of voice impersonation attacks, with similar findings as to the above studies. Stanford History Education Group conducted a study [18] in which the participants (school/college students) were asked to find the differences in some media contents, e.g., news and ads, identify real-fake Facebook accounts, test the reliability of Facebook posts (whether a web site is trusted).…”
Section: Related Workmentioning
confidence: 67%
“…The first classical synthesis attack measurement paper [57] uses a traditional survey format and finds that users correctly distinguish between real and Festvoxsynthesized voices (imitating the real speaker) about 50% of the time, regardless of their familiarity with the real speaker. A followup study to this [60] uses the same data and survey format but includes fNIRS brain scanning technology to measure participants' neural activity. They find no statistically significant differences in neural activity when real or synthetic speakers are played.…”
Section: Voice-based Spoofing Attacksmentioning
confidence: 99%
“…Having demonstrated that DNN-synthesized speech can easily fool machines (e.g., real-world SR systems), we now move to evaluate their impact on humans. Different from prior work that uses surveys to measure human perception of speech synthesized by classical (non-DNN) tools [57,60], we assess the susceptibility of humans to DNN-synthesized speech in different interactive settings. For this we conduct two user studies, covering both static survey and "trusted" interaction settings.…”
Section: Synthesized Speech Vs Humansmentioning
confidence: 99%
See 1 more Smart Citation